Advances in Agricultural Engineering Technologies and Application (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Modernization in the agriculture sector is important to ensure food security and poverty alleviation, which are the primary themes of UN-SDGs. There are many challenges in developing advanced agricultural techniques, tools, and systems, by which sustainable agriculture and food security can be satisfied. Worldwide, agricultural mechanization and modernization can be attained with advancements in agricultural engineering technologies and their associated applications. The concept is directly linked to the technological advancements in agricultural automation and robotics; precision agriculture; high-efficiency irrigation systems; farm energy systems; handling, storage, and processing of agricultural products; livestock and poultry sheds; farm water/wastewater management; biomass, biogas, and biochar; remote sensing and geographical studies; societal aspects in agriculture; and the associated bioenvironment. Such advances in agricultural engineering technologies and applications are the need of the 21st century, particularly from the viewpoint of the agricultural water–energy–food security nexus. Therefore, this Special Issue comprises original research and review studies in the abovementioned research areas.